(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
The aim of the work is to present the theoretical applications of purchasing models that illustrate the satisfaction of purchasing needs. This analysis aims to show possible consumer behavior. The article presents selected issues in the field of the consumer, his needs, decisions and activities related to before and after the purchase.